The Effect of Fartlek Training on Endurance in Runners at the Semarak Athletic Center - Muhammad Okhy Stiawan; Suwarni Suwarni; Ajis Sumantri (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study was conducted to determine the effect of fartlek training on endurance in runners at the Semarak Athletic Center. The data analysis methods used included a normality test and a homogeneity test. Hypothesis testing was performed using a paired t-test because this study compared two sets of data from the same group, namely the pre-test and post-test results. The results of the study showed a calculated t-value of 6.463 with a significance level of 0.000. Since the significance level is less than 0.05, H₀ is rejected and H₁ is accepted. Based on these results, it can be concluded that fartlek training has a significant effect on increasing the VO₂max of runners at the Semarak Athletik Center Club in Bengkulu.